Lawyers, Archivists, and the Turn to Transparency in the French State - Ron Levi; Sophie Marois; Sara Dezalay (AJIL Unbound, 2024)
In 2021, the French government commissioned two reports on episodes of extreme violence involving France's past: the Algerian War and the Rwandan genocide. Both reports grapple with how “the past haunts the present and the future,”3 a theme that is central to Karen Knop's scholarly legacy. In both reports, legal, historical, and archival expertise are positioned to redraw and recast relations of France to Africa. We argue that the reports’ focus on the role of a particular class of experts (namely archivist and historians, rather than lawyers) reflects France's current approach to narrating historical injustice, emphasizing public memory of violent pasts, rather than legal responsibility of the French state.